Perception of risk of HIV infections and sexual behaviour of the sexually active university students in Zimbabwe - Nkomazana, Njabulo; Maharaj, Pranitha (Taylor & Francis, 2016)
The study sought to establish university students’ perceptions of risk of HIV infections. A cross-sectional survey was conducted on 345 sexually active students at two universities in Zimbabwe (one state and one private). Results revealed that above a quarter of the respondents felt at risk of getting HIV due to their regular partners’ sexual behaviours and more than half felt at risk of getting HIV due to their casual partners’ sexual behaviours. In addition, a third of the respondents acknowledged the HIV risk due to their own sexual behaviours. More state university respondents felt exposed to HIV infections due to own sexual behaviours than their private university counterparts. Despite these revelations, only 66.56% had earlier thought of their chances of getting infected with HIV. Personal HIV risk perceptions were low, reported by 27.76% of the sexually active respondents. Almost all respondents described their fellows’ sexual behaviours as either risky or very risky.